Understanding inclusive entrepreneurship ... : فهم ريادة الأعمال الشاملة ... - Nafisa Yeasmin; Waliul Hasanat (OpenAlex, 2022)
A recent OECD report recognises that the limited scope for immigrant women to integrate into mainstream Finnish society has kept them out of the labour market. In fact, a woman with migrant background faces several challenges to get access to the Finnish labour force and this has prompted them to become self-employed in small business, particularly in the northern part of Finland. However, establishing a small business and its operation induces diverse problems in this remote, mainly rural region. An inclusive entrepreneurship policy may support improving their condition in entrepreneurship. The study explores the main factors hindering the financial and socio-cultural inclusion of women immigrants in Northern Finland. A thematic analysis of cultural and economic inclusivity, based on descriptive phenomenology, helps understand and reconstruct a policy of inclusive societies in the context of rural entrepreneurship. ... : يعترف تقرير حديث لمنظمة التعاون الاقتصادي والتنمية بأن النطاق المحدود للنساء المهاجرات للاندماج في المجتمع الفنلندي السائد قد أبقاهن خارج سوق العمل. في الواقع، تواجه المرأة ذات الخلفية المهاجرة العديد من التحديات للوصول إلى القوى العاملة الفنلندية، مما دفعها إلى العمل لحسابها الخاص في الأعمال التجارية الصغيرة، لا سيما في الجزء الشمالي من فنلندا. ومع ذلك، فإن إنشاء شركة صغيرة وتشغيلها يؤدي إلى مشاكل متنوعة في هذه المنطقة النائية، ولا سيما الريفية. قد تدعم سياسة ريادة الأعمال الشاملة تحسين حالتهم في ريادة الأعمال. تستكشف الدراسة العوامل الرئيسية التي تعيق الإدماج المالي والاجتماعي والثقافي للمهاجرات في شمال فنلندا. يساعد التحليل المواضيعي للشمولية الثقافية والاقتصادية، بناءً على الظواهر الوصفية، على فهم وإعادة بناء سياسة المجتمعات الشاملة في سياق ريادة الأعمال الريفية. ...